Catalytic hydrogen evolution reaction on surfaces of metal-nanoparticle-coated zinc-based oxides by first-principles calculations. (12th December 2022) - Tseng, Wei-Che; Chang, Chia-Wei; Kaun, Chao-Cheng; Su, Yen-Hsun
Abstract: Using first-principles calculations, we investigate the hydrogen evolution reaction (HER) on the noble-metal-nanoparticle-coated zinc or zinc-tin oxide surfaces. Among the six catalytic structures, the adsorption free energy of Au/ZnO structure is closest to zero. The relative energy diagrams reveal that Volmer-Heyrovsky mechanism on the NP (oxide) reactive site dominants the HER process on NP/ZTO (Pt/ZnO and Au/ZnO) structures. However, comparing the adsorption free energy and primary energy barrier of the prefer path of each structure, the Pt/ZnO structure shows the best performance for the HER process. Highlights: The HER performance of NPs-coated oxide were studied by first principle calculation. The NPs surface of Au/ZnO structure shows the lowest adsorption free energy. Pt cluster is the preferred surface for hydrogen spillover according to Bader charge. Volmer-Heyrovsky mechanism on NPs surface of Pt/ZnO has the best HER performance.